VIDEO PROMOSI WISATA KUAU KULIEK NAGARI SUNGAI BULUAH - YODI OKTAVIANUS, Dr. M. Nasrul Kamal, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Nagari Sungai Buluah Tourism is a natural tourism destination in the Padang Pariaman Regency which has two tourist attractions namely Sarasah Kuau waterfall and kuliek tree house. However, the lack of information about Nagari Sungai Buluah tourist attractions and the absence of use of video media by the management in promoting Nagari Sungai Buluah tourism objects, has made tourists or people outside the area not know in detail about tourism and what activities can be enjoyed.Promotional videos of Nagari Sungai Buluah are inseparable from communicative and informative media so that they can be reached by the wider community. This promotional video contains documentation of the trip to the tourist attraction of sarasah kuau waterfall and kuliek tree house. The purpose of the design is to get an effective and communicative video design to introduce and provide information about tourism in Nagari Sungai Buluah. This promotional video is made using qualitative research methods withThe data analysis method used in this promotional video is through the 5W + 1H analysis approach (what, who, when, where, why and how). The data collection method used was documentary observation and interviews with officers at the Padang Pariaman District Youth and Sport Office and Benny Parmadi tourism awareness group (Pokdarwis). This promotional video is also supported by several supporting media such as posters, sign systems, T-shirts, totebags, stickers, mugs and CD covers, can be customized.Keywords:Video,Promotion,KuauKuliek,Nagari,Sungai,Buluah